The role of sirtuins in dermal fibroblast function - Gilbert, Michael M.; Mathes, Samuel C.; Mahajan, Avinash S.; Rohan, Craig A.; Travers, Jeffrey B.; Thyagarajan, Anita (Frontiers in Medicine, 2023)
The sirtuins are a family of seven proteins that perform a variety of dermatological functions and help maintain both the structure and function of the skin. More specifically, the sirtuins have been shown to be altered in multiple dermal cell types including dermal fibroblasts. The functions of dermal fibroblasts are extensive and include playing a significant role in wound healing as well as helping to maintain the integrity of the skin. As dermal fibroblasts age, they can undergo a state of permanent cell cycle arrest, known as cellular senescence. This senescent process can occur as a result of various stressors, including oxidative stress, ultraviolet radiation-induced stress, and replicative stress. In recent years, there has been a growing interest in both enhancing the cutaneous fibroblast’s ability to facilitate wound healing and altering fibroblast cellular senescence. Thus, in this review, we examine the relationship between sirtuin signaling and dermal fibroblasts to understand how this family of proteins may modulate skin conditions ranging from the wound healing process to photocarcinogenesis associated with fibroblast senescence. Additionally, we offer supporting data from experiments examining the relationship between fibroblast senescence and sirtuin levels in an oxidative stress model indicating that senescent dermal fibroblasts exhibit diminished sirtuin levels. Furthermore, we survey the research on the role of sirtuins in specific dermatological disease states where dermal fibroblast function has been implicated. Finally, we conclude with outlining potential clinical applications of sirtuins in dermatology. In sum, we find that the literature on the involvement of sirtuins in dermal fibroblasts is limited, with research still in its early stages. Nevertheless, intriguing preliminary findings merit additional investigation into the clinical implications of sirtuins in dermatology.